History of mountain warfare - Markus Tannheimer; Raimund Lechner (University of Applied Sciences in Tarnow, Poland, 2022)
Mountain warfare has thousands of years of history and presents numerous challenges to military operations. History proves, that this environment has decreased combat strength, caused more casualties than the enemy in some operations and influenced war tactics significantly. Mountain warfare has an increasing frequency due to withdrawal areas for hostile forces, being home of ethnic minorities, being origin of many water supplies and being a natural frontier between countries. Mountains influence all warfighting functions, but especially movement and manoeuvre (mobility) and force protection (health support). To overcome the hardships of mountain warfare, special mountain units including support elements are mandatory, especially for health service support.